Paciente femenino de 53 años con neumonía bacteriana. - Castro Fajardo, Lady Jasmin (2021)
We present a case of a 53-year-old female patient who went to the emergency area due to a clinical picture of approximately 1 day of evolution characterized by chest pain, shortness of breath, cough with greenish expectoration, fever and chills. Upon admission, the patient is awake and oriented. Despite the limitations, they were able to carry out the clinical and imaging diagnosis of the patient.